A comparative citation analysis study of master's theses at the American University of Beirut, Lebanon. Issue 4 (3rd October 2016) - Ahmadieh, Dima; Nalbandian, Salpy; Noubani, Khaled
Abstract : Purpose: The purpose of this paper is to determine and compare the type and age of cited literature in master's theses of three academic disciplines at the American University of Beirut (AUB), Lebanon. It also aims to improve the existing monograph and serial collections at AUB. Design/methodology/approach: As theses and dissertations present a convenient source of bibliographies for examination, the authors conducted a citation analysis of all master's theses completed during the period 2004-2013 in the disciplines of biology, mechanical engineering and political science. Bibliographic data were extracted from each citation in the reference list(s) and later analyzed using Microsoft Excel. Availability of all cited books and journals was checked against the library catalog. Findings: This case study reveals the extent to which the AUB University Libraries (UL) collections answer the research needs of graduate students. The findings show that engineering and biology students use a significantly greater number of scholarly journal articles than political science students, while all disciplines rely on recent publications. Practical implications: This paper's findings will prove useful to develop lists of core journals for the AUB UL. The findings will help managing existing collections and provide a base for informed decision-making as regards journal subscriptions and cancellations. Originality/value: Although many citation analyses of master's theses have been done around the world, this study is one of the few completed in the Arab world. Hence, it offers useful insight for collection development in Lebanon and the Arab world.